Переописание Avocettolepis vaginata (Cestoda, Hymenolepididae) - Корнюшин, В.В.; Спасский, А.А. (Вестник зоологии, 1983)
Avocettolepis vaginata (Baczynska, 1914), a specific avocet parasite, is described in detail and illustrated. Important uncertainties of the original description are corrected, redescription of the type material from Egypt (Deblock, 1964) is supplemented.